Perangkat Sistem Parkir Otomatis Berbasis Sistem Minimum - Anton Yunus Timothy Adichandra; Hendra Tjahyadi; Arnold Aribowo (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2015)
Abstract— An automatic parking system miniature modeldesign and implementation is reported in this paper. The systemis a minimum based system using Near Field Communication(NFC) technology, and connected to a database server. Thesystem can be divided into two subsystems, namely a decision andcontrol system, and database server system. Furthermore, thedecision and control system can be divided into two elements: (i)Element 1 which consists of LCD module, NFC module, andEthernet module, and (ii) Element 2 which consists of LCDmodule and stepper motor driver module. The two elements areconnected through a wireless connection using XBee wirelessdevice. To implement the NFC feature, NFC Shield V2.0manufactured by Seed Studio is used. As an initial process, allNFC tags and cards are registered to the database server system.Then the parking process is starting with the detection of NFCtags or cards in Element 1 of the decision and control system.Based on the detection results and the results of querying thedatabase server a decision is then send to Element 2 that willmove the lift to the designated parking lot. In that sense, thesystem is able to allocate the parking space to its users who havethe registered card or tag. Freetronics EtherMega v3.0 is used asthe central processing unit for the system which is used forquerying the database and take actions based on that queryresults. An integrated Ethernet chip on EtherMega is used toconnect the decision and control system to the database serversystem, because the system can connect directly to the databaseserver. A computer that is usually needed to be the middle manfor procession queries is no longer needed. From a number oftests performed, the system works well and can achieve 100%allocation success rate. The system is able to allocate the parkinglot very well and to check whether the lot is occupied or free. Thesystem can also control the lift to move to the appropriate lot.Observed weakness is that the system’s stability is affected byheat generated by the system itself.Keywords—wireless, database, automatic parking, feedforward,RFID